Auxiliary‐Directed C(sp3)−H Arylation by Synergistic Photoredox and Palladium Catalysis. Issue 58 (21st September 2017) - Czyz, Milena L.; Lupton, David W.; Polyzos, Anastasios
Abstract: Herein we describe the auxiliary‐directed arylation of unactivated C(sp 3 )−H bonds with aryldiazonium salts, which proceeds under synergistic photoredox and palladium catalysis. The site‐selective arylation of aliphatic amides with α‐quaternary centres is achieved with high selectivity for β‐methyl C(sp 3 )−H bonds. This operationally simple method is compatible with carbocyclic amides, a range of aryldiazonium salts and proceeds at ambient conditions. Abstract : Of earth and light : An auxiliary‐directed arylation of unactivated C(sp 3 )−H bonds with synergistic photoredox and palladium catalysis is reported. This approach enables the site‐selective arylation of aliphatic amides with α‐quaternary centers and high selectivity for β‐methyl C(sp 3 )−H bonds. The operationally simple method is compatible with a range of amides, aryldiazonium salts and proceeds at room temperature.